Mediated Images of the South : the Portrayal of Dixie in Popular Culture. - Slade, Alison F. (Lexington Books, 2012)
Mediated Images of the South: The Portrayal of Dixie in Popular Culture, edited by Alison Slade, Dedria Givens-Carroll, and Amber Narro, seeks to explore and understand the impact of the image of the Southerner within mass communication and popular culture by looking at images in politics, film, television, public relations, advertising, sports and social media. While there is a long list of successful southern politicians, historical figures, businessmen and women, actors and actresses, sports figures and other national and world leaders, this edited collection finds that there is still work.